The Effect of Transcendental Meditation on the Immune Response of Bali Mandara High School Students - Novitasari Novitasari; Kartika Sari; Putu Asih Primatanti; Saktivi Harkitasari; I Gusti Ngurah Dwija Putra; Irawan Sukma (Health Science Journal of Indonesia, 2022)
Background:Meditation has become an increasingly popular form of alternative medicine. Many studies have been conducted to assess the health benefits of meditation. In particular, Transcendental Meditation (TM) has been shown to be effective in treating psychological disorders, hypertension, cardiovascular disease, and high cholesterol. Methods: This study has a total sample of 150 students. The study group consisted of 3 groups; control group, TM group 1 (students who regularly practiced TM for 1 year), TM group 2 (students who regularly practiced TM for 2 years). TM Group consists of 50 students for each group. The control group consisted of 50 students who did not use any relaxation techniques. Total eosinophils, neutrophils, lymphocytes, monocytes and hematocrit are counted by an automated quantitative hematology analyzer. Results: The results showed high rates of depression, anxiety and stress among the control group compared to the TM 1 and TM 2 groups. The levels of immune cells indicated that the TM 2 group differed significantly from the control group and the TM 1 group on eosinophils, monocytes and hematocrit (P < 0.05), whereas leucocytes, neutrophils, and lymphocytes showed an increase although no significant differences were observed in the TM 2 group (P> 0.05). Furthermore, there was a strong correlation between the immune response cells (leucocytes, lymphocytes, eosinophils, monocytes, leucocytes, and hematocrit) of the TM group. immune response correlates with increased meditation duration. Conclusion: Based on the results, meditation can help students to reduce depression, anxiety and stress. This study provides information that Transcendental Meditation has health benefits, especially in boosting the immune system.